The value of growth differentiation factor 15 as a biomarker for peripheral artery disease in diabetes patients - Wan-Chi Chuang; Chih-Hsun Chu; Cai-Sin Yao; Mei-Chih Wei; I-Lun Hsieh; Chia-Mei Liao (Diabetology & Metabolic Syndrome)
Abstract Background Growth differentiation factor 15 (GDF15) is significantly correlated with glycolipid metabolic disorders. Increased GDF15 levels are associated with obesity, insulin resistance, and diabetes as well as a poorer diabetes progression and prognosis. This is a prospective cohort study investigated the association between circulating GDF15 and diabetic peripheral artery disease. Methods A total of 174 diabetic patients aged 20–80 were enrolled. Plasma GDF15 levels were measured using ELISA. Peripheral Artery Disease (PAD) was evaluated with the Ankle brachial index (ABI) and the Cardio-ankle vascular index (CAVI). Results We found that diabetic patients with higher serum GDF15 levels (mean: 2521.5 pg/mL) had a higher incidence of peripheral artery disease. Multivariate logistic regression analysis indicated that patients with high serum GDF15 levels were at an increased risk of developing peripheral artery disease. High GDF15 levels were associated with ABI < 0.9 (right and left mean 19.5% p = 0.80, OR:1.13; 95%CI: [0.44–2.90]). Increased age (p = 0.025 OR:1.02; 95% CI [0.13–0.87]), family history (p = 0.001 OR:1.37; 95%CI: [0.37–5.05]), heart failure (p = 0.002 OR:4.96; 95%CI: [1.76–13.97]), sodium-glucose linked transporter 2 (SGLT 2) inhibitor use (p = 0.026), estimated glomerular filtration rate (eGFR) (p = < 0.001), and uric acid (p = < 0.001) was also positively associated with high GDF15 levels. Urine albumin-to-creatinine ratio (UACR) (p = < 0.010) was associated with higher GDF15 levels after one year of follow up. Conclusions Elevated GDF15 was significantly associated with worsening metabolic parameters and an increased risk of peripheral artery disease. Thus, it may be a stronger predictor of these outcomes in people with diabetes.